2023
DOI: 10.3390/microorganisms11020369
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles: Bactericidal and Mechanistic Approach against Drug Resistant Pathogens

Abstract: This review highlights the different modes of synthesizing silver nanoparticles (AgNPs) from their elemental state to particle format and their mechanism of action against multidrug-resistant and biofilm-forming bacterial pathogens. Various studies have demonstrated that the AgNPs cause oxidative stress, protein dysfunction, membrane disruption, and DNA damage in bacteria, ultimately leading to bacterial death. AgNPs have also been found to alter the adhesion of bacterial cells to prevent biofilm formation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 239 publications
1
49
0
Order By: Relevance
“…25 Ag NPs are known for their antimicrobial properties and inhibit scale formation by disrupting bacterial biofilms that promote scale deposition. 26 WO 3 NPs have a high surface area, high catalytic activity, and good stability, making them an ideal candidate for scale inhibition applications. 15,27 In this study, solid scale inhibitors based on silver tungstate NP-loaded 3D mesoporous KIT-6 were synthesized and their scale inhibition properties were studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Ag NPs are known for their antimicrobial properties and inhibit scale formation by disrupting bacterial biofilms that promote scale deposition. 26 WO 3 NPs have a high surface area, high catalytic activity, and good stability, making them an ideal candidate for scale inhibition applications. 15,27 In this study, solid scale inhibitors based on silver tungstate NP-loaded 3D mesoporous KIT-6 were synthesized and their scale inhibition properties were studied.…”
Section: Introductionmentioning
confidence: 99%
“…25 Ag NPs are known for their antimicrobial properties and inhibit scale formation by disrupting bacterial biofilms that promote scale deposition. 26 WO 3 NPs have a high surface area, high catalytic activity, and good stability, making them an ideal candidate for scale inhibition applications. 15,27…”
Section: Introductionmentioning
confidence: 99%
“…92 According to several studies, SNMs can exert their antibacterial action externally (membrane lysis, cell-wall disruption) or internally (inhibition of DNA replication or protein synthesis). 93 The probable mode of action of the three hydrogels (Ag-NPs@ SHGel-MoS 2 , Ag-NPs@SHGel-MoSe 2 , and Ag-NPs@SHGel-MoS 2 -MoSe 2 ) was investigated.…”
Section: (B)) Stem Edxmentioning
confidence: 99%
“…This outcome is unexpected because E. coli is a G−ve bacterium with a lipopolysaccharide-containing outer membrane less susceptible to antimicrobial agents' penetration, as compared to G+ve S. aureus. 45,46 Conversely, Ahmad et al 47 and More et al 48 have demonstrated that the thinner peptidoglycan cell wall of G−ve bacteria is more liable to Ag NPs than their G+ve counterparts. The later possess a thick peptidoglycan layer that can act as a barrier for the cell penetration of Ag NPs and their released Ag + ions.…”
Section: Uv−vis Absorption and Xrdmentioning
confidence: 99%